2014
DOI: 10.1039/c4ra04258a
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun nanofibers of p-type BiFeO3/n-type TiO2hetero-junctions with enhanced visible-light photocatalytic activity

Abstract: One-dimensional BiFeO 3 /TiO 2 heterostructure nanofibers with high visible-light photocatalytic activity have been successfully obtained via a facile hydrothermal process followed by an electrospinning technique. The results show that the BiFeO 3 /TiO 2 nanofibers are as long as dozens of micrometers with the diameters of about 100-300 nm, where BiFeO 3 nanoparticles are surrounded by anatase-type TiO 2 nanocrystals. Compared with the corresponding pure BiFeO 3 nanoparticles, and TiO 2 nanofibers, the asprepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…The VB and CB position of TiO 2 and BFO at point of zero charge on standard hydrogen electrode scale (ca 4.5 eV) can be calculated by E VB = X -E e + 0.5 E g and E CB = E VB -E g , respectively. Thus, the E VB levels for TiO 2 and BFO stand at 3.0 and 2.28 eV, respectively, and their E CB levels are positioned at -0.2 and +0.21 eV [17,37]. Thus, the energy gap (Eg) between the TiO 2 E CB and the BFO E VB is 2.48 eV, corresponding to the light energy of 500 nm by the equation: λ=1240/Eg.…”
Section: Discussion On Mechanismmentioning
confidence: 98%
See 3 more Smart Citations
“…The VB and CB position of TiO 2 and BFO at point of zero charge on standard hydrogen electrode scale (ca 4.5 eV) can be calculated by E VB = X -E e + 0.5 E g and E CB = E VB -E g , respectively. Thus, the E VB levels for TiO 2 and BFO stand at 3.0 and 2.28 eV, respectively, and their E CB levels are positioned at -0.2 and +0.21 eV [17,37]. Thus, the energy gap (Eg) between the TiO 2 E CB and the BFO E VB is 2.48 eV, corresponding to the light energy of 500 nm by the equation: λ=1240/Eg.…”
Section: Discussion On Mechanismmentioning
confidence: 98%
“…It is confirmed that the diffraction peaks of TiO 2 are ascribed to the anatase phase (JCPDS Card No. 21-1272) [17].…”
Section: Structural Characterization and Morphologymentioning
confidence: 96%
See 2 more Smart Citations
“…BiFeO 3 is a typical perovskite material with rhombohedral structure and one kind of the multiferroic materials which exhibit both ferroelectricity and magnetic ordering at room temperature [8,9]. BiFeO 3 material has been regarded as a promising photocatalyst due to its proper band gap (2.2-2.7 eV), which allows its visible light response [10][11][12]. In general, synthetic methods of BiFeO 3 materials include hydrothermal method, sol-gel, pulsed laser deposition, coprecipitation method, etc [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%